Organizational Justice, Citizenship Behavior, and Teacher Performance in Islamic Secondary Education: An Evidence from Indonesian Madrasah - Dian Dian; U Abdullah Mu'min; Anisa Siti Khodijah (Jurnal Ilmiah Peuradeun, 2026)
Improving teacher performance remains a critical challenge in Islamic secondary education, particularly in relation to organizational conditions that shape professional behavior and instructional effectiveness. This study investigated the extent to which organizational justice and Organizational Citizenship Behavior (OCB) jointly influenced teacher performance in State Islamic Senior High Schools (Madrasah Aliyah Negeri) in Sumedang Regency. Employing a quantitative research design, data were collected from MAN teachers and analyzed using inferential statistical techniques, including simultaneous F-tests and coefficients of determination. The results demonstrated that organizational justice and OCB exerted a significant positive influence on teacher performance (F = 48.457; p < 0.001), accounting for 57.7% of the variance. Among performance indicators, timeliness emerged as the strongest con tributor, reflecting a culture of discipline, while the quantity of work indicated areas requiring institutional improvement. Beyond confirming established theories of organizational behavior theories, the findings highlighted the contextual importance of integrating Islamic ethical values, such as amanah (trustworthiness), ukhuwah (brotherhood), and ihsan (excellence), into madrasah governance. By aligning fair organizational structures with value-based voluntary behavior, this study offers an empirically grounded and culturally embedded perspective for strengthening teacher performance and advancing sustainable educational quality in Islamic schooling contexts.